A novel polysaccharide obtained from Siraitia grosvenorii alleviates inflammatory responses in a diabetic nephropathy mouse model via the TLR4-NF-κB pathway. Issue 19 (13th August 2021) - Gong, Pin; Cui, Dandan; Guo, Yuxi; Wang, Mengrao; Wang, Zhineng; Huang, Zihan; Yang, Wenjuan; Chen, Fuxin; Chen, Xuefeng
Abstract : Leukotriene 3 and arachidonic acid are potential biomarkers, indicating inflammatory is involved in the occurrence of DN. SGP-1-1 alleviates the inflammatory response in DN mice by downregulating the TLR4-NF-κB pathway. Abstract : The inflammatory and antioxidant effects of a novel Siraitia grosvenorii polysaccharide (SGP-1-1) were investigated in an inflammation-suppressed diabetic nephropathy (DN) mouse model, and the underlying molecular mechanisms of inflammation and oxidative stress in SGP-1-1-treated mouse models were elucidated. The results demonstrated that DN mouse models treated with SGP-1-1 (50, 100, and 200 mg kg −1 d −1 ) exhibited good inflammation-modulating activity. In addition, histopathological analysis showed that glomerular atrophy, severe glomerular thylakoid hyperplasia, tubular endothelial detachment, basement membrane exposure, cytoplasmic infiltration with inflammatory cells, and interstitial oedema were all alleviated in DN mice after treatment with SGP-1-1. Metabolomics analysis based on UPLC-Q-TOF/MS revealed that a close relationship between the occurrence of DN and the potential 39 biomarkers, especially, leukotriene E3 and arachidonic acid, of which the main invloved metabolic pathways may beglycerophospholipid metabolism, arachidonic acid metabolism and primary bile acid biosynthesis. Quantitative real-time polymerase chain reaction (qRT-PCR) and western blot analysis results demonstrated that SGP-1-1 downregulates mRNA and the protein expression of the G protein-coupled cell membrane receptor TLR4 and its downstream protein kinase (NF-κB p65). This, resulted in the inhibition of the TLR4-NF-κB pathway in the peritoneum of DN mice by regulating inflammation, while stimulating the production of superoxide dismutase (SOD) and reducing the production of cytokine (IL-6, TNF-α) and malondialdehyde (MDA).